Sustentabilidade empresarial aplicada à construção civil : identificação de estratégias para implantação - Marques, Cristian Teixeira (2018)
The search for sustainable development puts the already built environment in a delicate position, by the means that the sector of the civil construction is strategic and builds one of the main backbones for the economic development and well-being promotion. The civil construction is an industry that has a negative view on itself because of the environmental impacts by its own making. These impacts are of a great variety and depend on a huge productive chain that goes all the way from raw materials extraction to the completion of the undertaking. Standing before all the tenders that come up daily throughout the pursuit to enhance the standards of sustainability in the productive chain of the work in construction, the following essay seeks going beyond the repetitive debate of a sustainable approach, to which is applied only the sustainable buildings and constructions. And to view sustainability in a doable fashion, through all the processes of an organization, it was intended to identify how the civil construction companies could sustainably improve themselves in the social, economic and environmental aspects, by the means of applying better practices. For that, the methodology was divided into three stages. First, a diagnosis was made in 12 construction companies in the city of Passo Fundo, in sight of sustainability, where the lack of understanding of the necessity to adopt the principles of sustainability in one’s activities became evident. Following up, with the research for benchmarks, good sustainable practices in the civil construction nationwide were identified, and those make up four macro actions which were evaluated by a decision-making group made up of 34 experts, and through an Analytic Hierarchy Process (AHP) the main action was chosen. This way, it can be concluded that one of the main obstacles faced inside organizations is the correct understanding surrounding sustainability and the reasons why it’s necessary, the uniformity amongst opinions for a bigger commitment among different stakeholders